Molecular basis of functional diversity of voltage-gated potassium channels in mammalian brain. - Stühmer, W (1989)
Cloning and sequencing of cDNAs isolated from a rat cortex cDNA library reveals that a gene family encodes several highly homologous K+ channel forming (RCK) proteins. Functional characterization of the channels expressed in Xenopus laevis oocytes following microinjection of in vitro transcribed RCK-specific RNAs shows that each of the RCK proteins forms K+ channels that differ greatly in both their functional and pharmacological properties. This suggests that the molecular basis for the diversity of voltage-gated K+ channels in mammalian brain is based, at least partly, on the expression of several RCK proteins by a family of genes and their assembly to homooligomeric K+ channels with different functional properties.